Adherence to an overweight and obesity treatment: the response evolution chart (2020)
Background. Overweight and obesity affect the psychosocial environment, because obese people experience social stigmatization, which most often limits and excludes them from society. In the treatment of overweight and obesity, diet is considered essential, although it must be integrated into a general program, with physical exercise, modification of lifestyle habits, and psychological support. However, even if weight reductions are achieved, only a small percentage of patients are able to maintain a healthy weight for a long period of time; hence, further studies are warranted to determine other appropriate motivational strategies that can help this patient group succeed in maintaining a healthy lifestyle. The aim of the study is to possibly relate visual changes in an obesity treatment. Methods. An observational clinical study was conducted among 110 adult overweight and obese patients who consulted a medical nutrition clinic for nutritional assessment and treatment to improve their aesthetic image and health status over a period of 1year. They were subject to a personalized weekly follow-up consultation over the course of 16weeks that included photographic body image control, which measures the patient's evolution response using an evolution chart. Results. Weight loss, reduction in waist circumference, and loss of visceral fat were found to be associated with linear changes in the Response Evolution Chart. Observing the response at the individual level, in men, weight loss, reduction in waist circumference, and loss of visceral fat were found to be associated with linear changes in the motivational picture; in women, only weight loss and reduction in waist circumference were found to be associated with linear changes in the motivational picture (p<0.05). Discussion.The most important finding in this study is that a relationship was found between weight loss, reduction in waist circumference, and loss of visceral fat, which can serve as a reference in the treatment of overweight or obesity patients regardless of sex. This change was observed in the Response Evolution Chart when the initial abdominal circumference was compared with that in the final photo (motivational picture). A 6-kg weight loss, a −1 point decrease in visceral fat index, and an 8.5-cm decrease in waist circumference were observed in one line. Greater losses with more lines were noted in the motivational picture.